Impact of Response to Hypomethylating Agent‐Based Therapy on Survival Outcomes in the Context of Baseline Clinical‐Molecular Risk and Transplant Status in Patients With Higher‐Risk Myelodysplastic Syndromes/Neoplasms: An analysis From the International Consortium for MDS (icMDS) - Benjamin Rolles; Jan Philipp Bewersdorf; Tariq Kewan; Ondrej Blaha; Jessica M. Stempel; Luca Lanino; Najla H. Al Ali; Amy E. DeZern; Mikkael A. Sekeres; Geoffrey L. Uy; Samuel Urrutia; Hetty E. Carraway; et al. (American Journal of Hematology, 2026)
ABSTRACT Baseline IPSS‐M risk, response to hypomethylating agent (HMA) therapy, and receipt of allogeneic stem cell transplant (allo‐HCT) have all been individually shown to impact overall survival (OS) in patients with myelodysplastic syndromes (MDS). However, the prognostic impact of response when adjusting for IPSS‐M risk and treatment strategy remains unclear. Hence, we used the VALIDATE database of the International Consortium for MDS (icMDS) to evaluate the impact of International Working Group (IWG) 2023 best response on OS in 715 HMA‐treated, higher‐risk MDS patients stratified by baseline IPSS‐M risk and their treatment strategy (subsequent allo‐HCT vs. medical therapy alone) treating both best response and allo‐HCT as time‐dependent variables. Baseline IPSS‐M risk (hazard ratio (HR): 0.5, p < 0.001) and receipt of allo‐HCT (HR: 0.5, p < 0.001) were the strongest independent predictors of OS, whereas achievement of composite complete response (cCR) had a more modest impact on OS (HR: 0.8, p = 0.004). Among patients treated with medical therapy alone, achieving cCR improved OS significantly (HR: 0.7, p = 0.006). In contrast, among transplanted patients, cCR did not retain independent prognostic value for post‐transplant survival after adjusting for baseline IPSS‐M (HR: 0.9, p = 0.634). Achieving cCR did not fully overcome adverse disease biology as OS continued to segregate according to baseline IPSS‐M risk. In summary, achieving cCR improves outcomes in non‐transplanted patients, but it does not significantly impact post‐transplant OS, suggesting that failure to achieve cCR with HMA may not warrant delay or preclude allo‐HCT. Clinical trials should consider response in the context of IPSS‐M risk distribution and treatment strategy (subsequent allo‐HCT vs. medical therapy alone) to avoid overinterpretation of high response rates.